Updated Bibliographic Review About the Hotel Service (2018) - Angamarca Izquierdo, Guillermo (2019)
This article deals with an updated bibliographical revision on the main theoretical conceptions of the hotel service, that reaches until the year 2018. Physical and digital publications have been included, coming from books, theses and scientific articles, related to it.  It was proposed as specific objectives to conceptualize: 1. The hotel service, 2. Characteristics of the hotel services and 3. Elements of the hotel service. The following conclusions were reached: hotel service is that aimed at providing temporary accommodation, through the interrelation between the client and the service employees, the physical resources or products and the systems of providing services, according to processes, procedures and behaviors, that generate additional services such as food, beverages and entertainment, communication, among others, whose purpose is to provide satisfaction according to the needs and desires of customers: the characteristics of the hotel service are: intangibility, inseparability, heterogeneity, perishability, integrality, seasonality, geographic origin of the clients, the plurality of communication channels, philosophy 24/365 and consumption of the service in the place of production; The elements of the hotel servucción are: the system of internal organization, the physical support and the personnel in contact, the client, the other clients and the service.